2013
DOI: 10.1371/journal.pone.0081468
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Identification of Mutant Alleles Derived from Lung Cancer in Plasma Cell-Free DNA via Anomaly Detection Using Deep Sequencing Data

Abstract: The detection of rare mutants using next generation sequencing has considerable potential for diagnostic applications. Detecting circulating tumor DNA is the foremost application of this approach. The major obstacle to its use is the high read error rate of next-generation sequencers. Rather than increasing the accuracy of final sequences, we detected rare mutations using a semiconductor sequencer and a set of anomaly detection criteria based on a statistical model of the read error rate at each error position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(98 citation statements)
references
References 29 publications
2
95
0
1
Order By: Relevance
“…This recommendation is evidence based and supported by 6 studies, 232,234,235,242,243,247 comprising 2 MAs, 243,247 2 PCSs, 235,242 and 2 PRCSs. 232,234 The identified studies used various EGFR detection methods, but all verified the results from cfDNA with results from tumor tissue. Using reported true-positive, false-positive, truenegative, and false-negative data from 4 studies, a metaanalysis was conducted to determine a pooled estimate of sensitivity and specificity for cfDNA detection of EGFR mutation ( Figure 3).…”
Section: Recommendationmentioning
confidence: 95%
See 3 more Smart Citations
“…This recommendation is evidence based and supported by 6 studies, 232,234,235,242,243,247 comprising 2 MAs, 243,247 2 PCSs, 235,242 and 2 PRCSs. 232,234 The identified studies used various EGFR detection methods, but all verified the results from cfDNA with results from tumor tissue. Using reported true-positive, false-positive, truenegative, and false-negative data from 4 studies, a metaanalysis was conducted to determine a pooled estimate of sensitivity and specificity for cfDNA detection of EGFR mutation ( Figure 3).…”
Section: Recommendationmentioning
confidence: 95%
“…231 Several studies 232,233 have shown comparable, if not superior, analytical sensitivity with droplet digital PCR, and NGS methods 234,235 can also provide this level of sensitivity, given the appropriate assay design. It is important, however, to recognize that unmodified Sanger sequencing, which was an acceptable method in the original 2013 guideline, 1 does not provide adequate sensitivity for this application.…”
Section: Recommendationmentioning
confidence: 99%
See 2 more Smart Citations
“…Ein Algorithmus, entwickelt von Narayan et al, in dem eine Konsensussequenz nach einer Paired-End-Sequenzierung über den überlappenden Bereich gebildet wird, konnte die Fehlerrate von 0,31 % pro Base auf 0,07 % verringern [56]. Mit demselben Ansatz konnte eine japanische Gruppe LODs von 0,01, 0,01 und 0,05 % für die Detektion der EGFR Hotspot Mutationen L858R, L861Q, und T790M aus Plasma erzielen [57,58].…”
Section: Introductionunclassified